Body image perception of pilates practitioners in the municipality of Ponto Belo-ES: A case study (International Seven Journal of Health Research, 2023)
Introduction: Body image consists of the multidimensional elaboration of the measurements, contours and shapes of the human body, correlating with the mental perception of how a person understands, feels and perceives themselves. One of the main activities used to improve the perception of body image is Pilates. Objective: to present the body perception of individuals who practice Pilates in the municipality of Ponto Belo, in the north of the state of Espírito Santo. Methodology: this is a descriptive, exploratory and quantitative study, where in the first instance a bibliographical survey was carried out and in the second, a field survey by means of a questionnaire applied to sixteen people practicing Pilates. Results: Pilates has the role of correcting body posture, toning muscles and improving motor stability, as well as playing a fundamental role in aesthetics and body image. Conclusion: At the end of the research, it was clear that the objective proposed in the study had been achieved, as it became clear to the readers the body perception of the individual who practices Pilates in the municipality of Ponto Belo, in the north of the state of Espírito Santo, and it was also possible to identify the opinion of the interviewees about their self-assessment of body image.